Bridging the Communication Gap: Pragmatics and Interactional Dynamics in Deaf and Hard of Hearing Children. - Mazzocconi, Chiara; Hidalgo, Céline; Hallart, Charlie; Roman, Stéphane; Bertrand, Roxane; Lancia, Leonardo; Schön, Daniele (Journal of Speech, Language & Hearing Research, 2026)
Purpose: Children who are deaf and hard of hearing (DHH) often face challenges in everyday social communication, even when they achieve good auditory recovery through hearing technologies. These difficulties, particularly in pragmatic and interactional domains, can affect peer relationships, educational outcomes, and quality of life. This study aims to characterize interactional and discourse-level challenges in DHH children with functional auditory access to inform targeted interventions. Method: We analyzed dyadic child-adult interactions involving nine DHH and 13 typically hearing (TH) children (ages 6-11 years), all using oral language. The DHH group included users of bilateral cochlear implants (CIs), bimodal devices (CI + hearing aid), and bilateral hearing aids. Each child interacted with an adult in a referential (treasure-hunting) task, alternated with child-led subtasks (e.g., storytelling). We adopted a multilevel analysis approach ranging from acoustics to pragmatics: acoustic features, turn-taking, laughter and their convergence, and dialogue acts. Results: Turn-taking and acoustic alignment (fundamental frequency, intensity, syllable rate) were similar across groups. However, dyads involving DHH children are less likely to complete the task, and DHH children produce significantly shorter turns and less speech laughter. They also showed significantly lower contingent responding to adult laughter and dialogue acts. Conversations with DHH children were more asymmetrical, with the adult speaking more, producing significantly longer turns, less laughter, and less laughter mimicry than when interacting with TH children. Conclusions: We provide a detailed, multilevel characterization of DHH conversational dynamics while interacting with a TH adult--whose behavior at times reduces interactional opportunities for the child. These findings highlight the dynamic nature of conversation and the importance of interventions that foster contingency, engagement, and mutual responsiveness to support DHH children's communicative development.